BIMBINGAN TEKNIS DAN OPTIMALISASI PENDAPATAN ASLI DAERAH MELALUI UPDATING DATA KOTA KENDARI - Adrian Tawai; Sartono Sartono; Syamsul Alam; Gunawan Gunawan; Arifin Utha; Samiruddin Samiruddin (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2022)
The development of the current administrative system of government is required not only to be efficient and effective but to strive for more synergy, especially from its governance. The shift of authority from the central government to local governments and then extended to the village level is a challenge but also an opportunity for bureaucrats to serve the community in a responsive manner. This condition requires an understanding of ideal and relevant governance in dealing with existing problems. This service generally aims to carry out technical guidance on optimizing local revenue through increasing the effectiveness of data updating and assessment of land and building tax objects in Kendari Caddi Village, Kendari City. The target audience for this activity are employees who are in Kendari Caddi Village using training, mentoring, guidance, and consultation on data validation practices which were carried out on 10 May 2022. The results of this activity resulted in (1) the effectiveness of data updating and tax object assessment activities. land and buildings in Kendari Caddi Village are quite good, (2) the role of the lurah in administrative activities, updating data, and assessing land tax objects is going well, and (3) services, rationality, effectiveness, and efficiency are running well.